Reference values for the external genitalia of full-term and pre-term female neonates. Issue 1 (19th June 2020) - Castets, Sarah; Nguyen, Kim-An; Plaisant, Franck; Prudon, Malika Baya; Plotton, Ingrid; Kassai, Behrouz; Roche, Sylvain; Ecochard, Rene; Claris, Olivier; Nicolino, Marc; Villanueva, Carine; Gay, Claire-Lise
Abstract : Background and objectives: Identifying virilisation of the genitalia in female newborns early during the neonatal period is important to diagnose pathologies. However, there is no clear threshold for clitoromegaly or for the anogenital ratio. The objective of this study was to define reference values for the external genitalia of full-term and pre-term female neonates. Design: This was a prospective study of all females born in the study centre between May 2014 and July 2016. Clitoral length and anogenital ratio were measured in 619 newborns with a gestational age of 24+2 to 41+3 weeks during their first 3 days of life. Associations between the values at day 3 and gestational age, birth weight and other newborn characteristics were examined by linear regression. Results: The mean clitoral length at day 3 of life was 3.69±1.53 mm (n=551; 95th percentile, 6.5 mm; maximum, 8 mm), and the mean anogenital ratio was 0.42±0.09 (95th percentile, 0.58). There was no significant variation with gestational age or birth weight, and no significant difference between the results at day 0 and day 3. Conclusion: These results suggest that clitoromegaly can be defined as a clitoral length >6.5 mm. Values ≥8 mm should prompt further investigations. An anogenital ratio >0.6 should be considered a sign of virilisation. Since clitoral size does not vary with gestational age or birth weight, clitoromegaly should not be attributed to prematurity.